HELIUM ISOTOPES IN SUBSURFACE FLUIDS FROM THE BAIKAL RIFT ZONE: AN APPLICATION TO THE PROBLEMS OF GEODYNAMICS - Polyak B.G. (My University, 2002)
The 3He/ 4He = R ratio was studied in underground fluids from 104 sites from the Baikal Rift Zone, BRZ, and adjacent areas in Russia and Mongolia. The R values vary from 1.0×E-8, typical of crustal radiogenic He, up to 1.1×E-5 just below the MORB characteristics. The repeated sampling of some sites and the comparison between the data for superficial springs and productive boreholes have shown no significant R variation in time or in depth.The lowest R values belong to CH4-rich gases. The more diverse R values were measured in N2- and CO2- rich fluids, and the latter show the highest R. Judging from N2/Aratm ratio, N2-rich gases are of atmospheric origin. The fN2/fNe ratio value in CO2- rich fluids indicates the excess (non-atmospheric) nitrogen. The comparison of the R values with He concentrations and predominate components of a fluid gas phase shows that this phase is formed under the effect of solubility-controlled fractionation in gas–water system and a gain/loss of chemically active gases within the crust. The distribution of R values across the BRZ strike indicates a discharge of heat-mass flux from the mantle not only inside the BRZ but also far to the east. Inside the BRZ, the range of R values is widest: from 4.9×E-8 to 1.1×E-5. These variations are regular: R values diminish along the BRZ strike in both directions from the Tunka Basin considered as a center of rifting. The decrease is accompanied by some decay of heat flow density and shows a reduction of heat-mass flux from the mantle in peripheral segments of the rift zone. The comparison of this trend with the data for other active continental rifts and mid-oceanic ridges suggests radically different mechanisms of mantle-crust interaction during oceanic spreading and continental rifting.
Keywords: He-isotopes; thermal waters; continental rifts; Baikal Lake